Recreational Fee Demonstration Program Retaining the Program?. - Library of Congress. Congressional Research Service ([S.l] : [s.n.], 2004)
Discusses the recreational fee demonstration program, which allows the Forest Service, National Park Service, Bureau of Land Management, and Fish and Wildlife Service to test the feasibility of charging fees at recreation sites to recover some of the costs of operating those sites; and addresses whether to retain program.
Record is based on bibliographic data in ProQuest U.S. Congressional Research Digital Collection (last viewed Dec. 2010). Reuse except for individual research requires license from ProQuest, LLC.
CRS Report.
Keywords: Recreation; User charges